Pengembangan Media Flipchart Bergambar untuk Materi Roll Belakang dalam Senam Lantai - I Komang Pastika; I Made Satyawan; Ni Luh Putu Spyanawati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The present research focused on the development of a pictorial Flipchart learning medium intended to facilitate instruction in the backward roll component of floor gymnastics for fourth-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Prior to student evaluation, the developed Flipchart underwent a series of expert assessments involving subject matter specialists, media experts, instructional design experts, and a physical education practitioner, followed by individual, small-group, and field-based trials. The validation results indicated that the developed Flipchart achieved very high feasibility ratings, while student evaluations also demonstrated highly positive responses across all trial stages. The findings suggest that the pictorial Flipchart is appropriate for supporting physical education instruction by presenting movement sequences in a clear, engaging, and systematic manner. This learning medium can serve as a practical alternative for improving students’ understanding of backward roll techniques, particularly in schools with limited technological resources.